2002
DOI: 10.1093/pubmed/24.2.120
|View full text |Cite
|
Sign up to set email alerts
|

Are socio-economic inequalities in mortality decreasing in Trent Region, UK? An observational study, 1988-1998

Abstract: There appear to be decreases in socio-economic inequalities in mortality between 1988 and 1998 in Trent Region. These trends run counter to those described in the majority of recent literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…show that the gap between the most and least deprived areas has also widened between 1981 and 2001 for the whole of Scotland. Conversely, one study has suggested that the mortality gap between small areas in one region of Britain (Trent) has not been widening over time (Strong et al, 2002). However, Rees et al's ( 2003) more recent work demonstrates that, once careful attention is paid to the calculation of appropriate population denominators, the gap can be seen to be widening.…”
Section: Introductionmentioning
confidence: 99%
“…show that the gap between the most and least deprived areas has also widened between 1981 and 2001 for the whole of Scotland. Conversely, one study has suggested that the mortality gap between small areas in one region of Britain (Trent) has not been widening over time (Strong et al, 2002). However, Rees et al's ( 2003) more recent work demonstrates that, once careful attention is paid to the calculation of appropriate population denominators, the gap can be seen to be widening.…”
Section: Introductionmentioning
confidence: 99%